ESG factors integration into corporate credit ratings : current state & impact of the CSRD - Lernoux, Marion (2024)
This thesis explores the impact of the Corporate Sustainability Reporting Directive (CSRD) on the integration of Environmental, Social, and Governance (ESG) factors into corporate credit ratings within the EU. Through interviews with key stakeholders, the study evaluates how EU-registered credit rating agencies (CRAs) assess the creditworthiness of EU-based companies, and explores the anticipated CSRD’s effect on non-financial information and corporate credit ratings. The findings reveal that ESG integration into corporate credit ratings across EU remains superficial, characterized by an undefined and subjective approach where ESG factors are often treated as secondary considerations that rarely influence final ratings. The primary obstacles include the lack of sufficient quality and comparability of non-financial information, particularly for smaller companies, along with a lack of tools and expertise to accurately assess their impact. Despite short-term uncertainties and compliances challenges, the CSRD is expected to achieve its long-term goals, by significantly improving the quality, availability, and comparability of ESG information, thereby addressing existing challenges in ESG incorporation for EU-registered CRAs. This enhanced reporting environment is expected to transform the quality of corporate credit ratings in the EU, significantly deepening ESG integration into credit analysis, and decision-making processes.